Teaching Materials for Reading in a Professional Context to Improve the Reading Skills of English Education Program Students - Sari, Ambar Wulan; Amalia, Nadra; Emelia, Tengku Winona; Arifin, Muhammad (Jurnal Penelitian dan Pengembangan Pendidikan, 2024)
Students expressed difficulty in dealing with unfamiliar vocabulary and complex sentence structures, which hindered their ability to identify important information and understand the message conveyed in the text. This research aims to develop a teaching tool called Reading for Professional Context that is appropriate to the cultural environment to improve the reading skills of students majoring in English education. This type of research is developed with a research design using the Graves model. The research subjects were two subject matter experts, two teaching materials experts, and two language experts. The trial subjects involved 22 students. Data collection methods use observation, interviews, and questionnaires. Data collection instruments with questionnaire sheets. Data analysis techniques use qualitative and quantitative analysis. The linear regression test is used to see the effect of teaching materials on reading skills. The results, namely the expert assessment, show that the product has excellent qualifications. The results of the linear regression test show that the use of "Reading for Professional Context" teaching materials significantly positively influences students' reading skills. It was concluded that the "Reading for Professional Context" teaching materials could improve students' reading skills. The findings from this research provide valuable insights for English language educators and curriculum developers in designing effective reading teaching materials to improve students' abilities in professional contexts.